2017
DOI: 10.1016/j.dsr2.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Aliphatic hydrocarbons and triterpenes of the Congo deep-sea fan

Abstract: Hydrocarbons were analyzed in sediments from the Congo River deep-sea fan, from the Congo River, and in sinking particles collected by sediment traps 40 m above the sediment. Studied sites encompassed three lobes of decreasing age of formation along the canyon: sites A, F and C and a another lobe system, disconnected from the active channel since 4 ka, Site E. Terrestrial long-chain odd n-alkanes were dominant in all sediments of the lobe system. Unsaturated terpenoids sourced by higher plants, such as gammace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 97 publications
(115 reference statements)
0
4
0
Order By: Relevance
“…As part of our ongoing research to identify bioactive substances from native mosses [18], we have recently isolated and identified for the first time a pentacyclic triterpene lup-20(29)-ene coming from Pilotrichella flexilis, which is a common species broadly distributed along Mexico [19], and barely one phytochemical study of an oversea species has been reported until now [20]. Structures related to this type of PTs mainly comprised in higher plants, have also been observed in other ecosystems, including deep-sea fan, ancient sediments from high-moor peats as well as in several geological sources [21,22].…”
Section: Introductionmentioning
confidence: 92%
“…As part of our ongoing research to identify bioactive substances from native mosses [18], we have recently isolated and identified for the first time a pentacyclic triterpene lup-20(29)-ene coming from Pilotrichella flexilis, which is a common species broadly distributed along Mexico [19], and barely one phytochemical study of an oversea species has been reported until now [20]. Structures related to this type of PTs mainly comprised in higher plants, have also been observed in other ecosystems, including deep-sea fan, ancient sediments from high-moor peats as well as in several geological sources [21,22].…”
Section: Introductionmentioning
confidence: 92%
“…Additionally, numerous sedimentological and organic geochemical data were obtained during the shore-based studies on the 145 sediment cores collected in different parts of the Congo turbidite system, from the canyon head to the terminal lobe complex, by ca. 5000 m of water depth (Droz et al, 1996(Droz et al, , 2003Gervais et al, 2001;Babonneau, 2002;Babonneau et al, 2002Babonneau et al, , 2004Babonneau et al, , 2010Ferry et al, 2004;Migeon et al, 2004;Bonnel, 2005;Treignier, 2005;Marsset et al, 2009;Rabouille et al, 2009Rabouille et al, , 2017aRabouille et al, , 2017bBaudin et al, 2010Baudin et al, , 2017aBaudin et al, , 2017bPicot, 2015;Stetten et al, 2015;Picot et al, 2016Picot et al, , 2019Croguennec et al, 2017;Méjanelle et al, 2017;Pastor et al, 2017;Pozzato et al, 2017;Schnyder et al, 2017;Taillefert et al, 2017). The resulting data allows a good description and understanding of the entire Congo turbidite system.…”
Section: Summary Of Recent Studies On the Congo Deep-sea Fanmentioning
confidence: 99%
“…5). Detailed organic geochemical investigations, including molecular signatures and palynofacies observations, were conducted in the upper and lower channellevee areas (Baudin et al, 2010) and in the terminal lobe complex (Stetten et al, 2015;Baudin et al, 2017b;Méjanelle et al, 2017;Pruski et al, 2017;Schnyder et al, 2017). All geochemical and palynological proxies suggest that at least 80-90% of the organic matter preserved in marine sediment along the turbidite channel has a terrestrial origin.…”
Section: Organic Matter Content In Recent Sedimentsmentioning
confidence: 99%
See 1 more Smart Citation